The impact of caries on human health - a review of knowledge - Tobor, Dominika; Grajek, Mateusz; Szlacheta, Patryk; Korzonek-Szlacheta, Ilona (Journal of Education, Health and Sport, 2022)
Dental caries is currently a huge social problem in many countries. Caries is a pathological process associated with the loss of minerals and the breakdown of the hard tissues of the tooth. The risk of its occurrence is very high, especially in children and adolescents. The development of caries is determined by the presence of plaque, the susceptibility of the tooth tissue, the substrate and the time factor. The state of oral health depends on a very age of factors, including hygiene habits, health-promoting education, prevention